2001
DOI: 10.1109/68.950746
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a dispersion-shifted fiber for simultaneous measurement of distributed strain and temperature through Brillouin frequency shift

Abstract: In this letter, we propose and realize a new method that utilizes a dispersion-shifted fiber having compound compositions with different temperature coefficients in core to simultaneously measure the distributed strain and temperature based on Brillouin frequency shift. In a 3682-m sensing length of large-effective-area nonzero dispersion-shifted fiber, a temperature resolution of 5 C, a strain resolution of 60 , and a spatial resolution of 2 m are achieved simultaneously.Index Terms-BOTDR, Brillouin frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 7 publications
1
47
0
1
Order By: Relevance
“…A preliminary method is to use a specially-designed fiber with multiple Brillouin peaks that exhibit different frequency variations in temperature and strain [15][16][17]. As shown in Fig.…”
Section: Multiple Peaks In a Specially-designed Optical Fibermentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary method is to use a specially-designed fiber with multiple Brillouin peaks that exhibit different frequency variations in temperature and strain [15][16][17]. As shown in Fig.…”
Section: Multiple Peaks In a Specially-designed Optical Fibermentioning
confidence: 99%
“…Although the preliminary method based on a specially-designed fiber [15][16][17] is a frequencybased measurement technique prior to the power-based one [22], it is still ill-conditioned and physically limited due to the correlated relationship among multiple peaks. …”
Section: Multiple Peaks In a Specially-designed Optical Fibermentioning
confidence: 99%
“…It was reported that 99.7% of the temperature error and 94% of the strain error is attributed to errors arising from the intensity measurement [2]. An elegant solution recently proposed by Lee et al [3] is to use large effective area fibre (LEAF), which has multiple composition fibre core. The Brillouin spectrum of silica fibre depends on it structure and doping composition of the fibre core.…”
Section: Introductionmentioning
confidence: 99%
“…A great part of distributed optical fiber sensors enables strain or temperature measurements. Those sensors allowing for simultaneous strain and temperature measurements are mostly based either on Brillouin scattering effect [2,3] or on combined Raman-Brillouin scattering effects [4], typically in conjunction with interrogating techniques based on optical time domain reflectometry (OTDR).…”
Section: Introductionmentioning
confidence: 99%